Religiusitas menghalangi kreativitas karyawan? Pemoderasian kepemimpinan transformasional - Hanuna Shafariah; Santi Retno Sari (LPMP Imperium, 2022)
Studies on religiosity, especially related to creativity, are still very limited. Therefore, this study aims to examine the effect of individual religiosity and transformational leadership as factors that increase employee creativity. The population of this research is company employees who are alumni of five private universities in Jakarta. A sample of 103 respondents was collected and given a questionnaire to collect data. The use of analysis techniques with macroprocess is an option in hypothesis testing. All hypotheses in this study were accepted with data support. The higher the employee's religiosity and the more transformational the leader, the higher the employee's creativity. The more transformational the leader, the stronger the effect of religiosity on employee creativity. Suggestions for practitioners should implement programs that are able to increase the religious level of employees and leaders with a transformational style.